Guideline on multimodal rehabilitation for patients with post-intensive care syndrome - Renner, Caroline; Jeitziner, Marie-Madlen; Albert, Monika; Brinkmann, Sabine; Diserens, Karin; Dzialowski, Imanuel; Heidler, Maria-Dorothea; Lück, Martina; Nusser-Müller-Busch, Ricki; Sandor, Peter S.; Schäfer, Andreas; Scheffler, Bettina; et al. (Critical care (London, England), 2023)
Background Intensive Care Unit (ICU) survivors often experience several impairments in their physical, cognitive, and psychological health status, which are labeled as post-intensive care syndrome (PICS). The aim of this work is to develop a multidisciplinary and -professional guideline for the rehabilitative therapy of PICS. Methods A multidisciplinary/-professional task force of 15 healthcare professionals applied a structured, evidence-based approach to address 10 scientific questions. For each PICO-question (Population, Intervention, Comparison, and Outcome), best available evidence was identified. Recommendations were rated as “strong recommendation”, “recommendation” or “therapy option”, based on Grading of Recommendations, Assessment, Development and Evaluation principles. In addition, evidence gaps were identified. Results The evidence resulted in 12 recommendations, 4 therapy options, and one statement for the prevention or treatment of PICS. Recommendations: early mobilization, motor training, and nutrition/dysphagia management should be performed. Delirium prophylaxis focuses on behavioral interventions. ICU diaries can prevent/treat psychological health issues like anxiety and post-traumatic stress disorders. Early rehabilitation approaches as well as long-term access to specialized rehabilitation centers are recommended. Therapy options include additional physical rehabilitation interventions. Statement: A prerequisite for the treatment of PICS are the regular and repeated assessments of the physical, cognitive and psychological health in patients at risk for or having PICS. Conclusions PICS is a variable and complex syndrome that requires an individual multidisciplinary, and multiprofessional approach. Rehabilitation of PICS should include an assessment and therapy of motor-, cognitive-, and psychological health impairments. Key points It is important to assess physical, cognitive, and psychological health functions of critically ill patients at risk for developing post-intensive care syndrome (PICS) during their stay in the ICU, their acute and rehabilitative inpatient and outpatient care. Physical health and motor function can improve through early mobilization, physical therapy, additional ergometer training (cycling) and neuromuscular stimulation. Before initiating oral nutrition, a standardized swallowing test should rule out risks of dysphagia and aspiration. Psychological health can improve through integrating relatives into care, keeping ICU diaries, and psychological care. Cognitive health can improve with prevention of delirium, early multimodal treatment of delirium, and/or attention training. Health care professionals must be sensitized and trained to recognize PICS.